Fertility and Welfare Under Demeny Voting - Grechyna, D; Vaithianathan, R (Elsevier BV, 2026)
This paper analyzes the welfare implications of children’s enfranchisement within a political economy framework that emphasizes the trade-offs in public policy when the electorate includes different age groups. We derive the political equilibrium under Markov strategies and compare welfare under standard suffrage and suffrage that includes children, for both PAYG and fully funded social security systems. The franchise that maximizes welfare across demographic groups depends on the fertility rate in the economy. Policies chosen when all demographic groups have voting rights are Pareto-improving compared to those chosen under the standard voting rights system, which excludes children from the electorate, when the fertility rate is low, and Pareto-reducing when the fertility rate is high. This result is driven by the surplus or shortage of funds available to finance pensions, depending on the ratio of workers to retirees in the economy. The model produces a negative association between tax revenues and fertility rates, as well as between public pension spending and the share of parents, consistent with OECD data. The counterfactual analysis based on the model calibrated to match the distribution of the number of children per household in OECD countries indicates that children’s enfranchisement would improve the welfare of all generations in most OECD countries.
Keywords: 38 Economics; 3801 Applied Economics; 3803 Economic Theory; 1401 Economic Theory; 1402 Applied Economics; 1403 Econometrics; Economics; 3502 Banking, finance and investment; 3801 Applied economics